ISLAMIC ECONOMIC MODEL AND THE PROBLEMS OF ITS APPLICATION IN RUSSIA - BEKKIN, Renat (CENTRAL ASIA AND THE CAUCASUS, 2006)
The world’s first Islamic bank, Mit Gamr Bank, was set up in 1963 in a place called Mit Gamr in Egypt. The bank, which functioned on the interest-free principle, marked the beginning of practical implementation of Muslim economic theories. At the same time, a Savings Corporation for Muslim Pilgrims (Tabung Hajji) was founded in Malaysia to help accumulate funds for hajj1 in accordance with the Muslim laws.2 In 1965, a Cooperative Investment and Financial Corporation appeared in Karachi (Pakistan). Simultaneously, several similar institutions which can be described as savings investment structures rather than commercial banks appeared in Egypt. On the whole, however, the experiment failed; very soon most of the institutions which sprang up haphazardly at the grassroots level in all corners of the Muslim East folded. The second wave of attempts at translating the Islamic economic ideas into practice under traditional (non-Muslim) economic conditions proved more successful. In 1975, the Dubai Islamic Bank began operating in the UAE, while the Organization of the Islamic Conference opened the Islamic Development Bank (IDB) with the intention of coordinating economic and social development of the Muslim communities throughout the world. In 1979, the world’s first Islamic insurance company was set up in Sudan. In some Muslim states, the faithful acquired the chance of paying zakat and ‘ushr (tithe) in a centralized way. Pakistan went as far as adopting a special law, the Zakat and ‘Ushr Ordinance, in 1980 to regulate the collection and distribution of taxes. Today, most countries with large Muslim communities have all sorts of institutions working on the basis of the Shari's. Russia is no exception.